Sinonasal pathophysiology of SARS‐CoV‐2 and COVID‐19: A systematic review of the current evidence - Gengler, Isabelle; Wang, James C.; Speth, Marlene M.; Sedaghat, Ahmad R. (Laryngoscope investigative otolaryngology, 2020)
Objective The ongoing pandemic of coronavirus disease (2019 coronavirus disease [COVID‐19]), caused by the Severe Acute Respiratory Syndrome Coronavirus 2 (SARS‐CoV‐2) virus, is highly contagious with high morbidity and mortality. The role of the nasal and paranasal sinus cavities is increasingly recognized for COVID‐19 symptomatology and transmission. We therefore conducted a systematic review, synthesizing existing scientific evidence about sinonasal pathophysiology in COVID‐19. Study Design Systematic review. Methods Systematic searches were performed of all indexed studies in PubMed/Medline and Cochrane databases through 28 March 2020 and studies searchable on preprints.com (including ArXiv and Scilit repositories) through 30 March 2020. Data extraction focused on sinonasal pathophysiology in COVID‐19. Results A total of 19 studies were identified. The sinonasal cavity may be a major site of infection by SARS‐CoV‐2, where susceptibility genes required for infection are expressed at high levels and may be modulated by environmental and host factors. Viral shedding appears to be highest from the nose, therefore reflecting a major source for transmission. This has been highlighted by multiple reports of health care‐associated infection (HAI) during rhinologic procedures, which are now consequently considered to be high risk for SARS‐CoV‐2 transmission to health care workers. While sinonasal symptomatology, such as rhinorrhea or congestion, appears to be a rarer symptom of COVID‐19, anosmia without nasal obstruction is reported as highly specific predictor of COVID‐19+ patients. Conclusion Sinonasal pathophysiology is increasingly important in our understanding of COVID‐19. The sinonasal tract may be an important site of infection while sinonasal viral shedding may be an important transmission mechanism—including HAI. Anosmia without nasal obstruction may be a highly specific indicator of COVID‐19. Level of Evidence 2a.